Use of non-invasive haemodynamic measurements to detect treatment response in precapillary pulmonary hypertension. Issue 9 (23rd June 2011) - Lee, Wai-Ting Nicola; Brown, Aileen; Peacock, Andrew John; Johnson, Martin Keith
Abstract : Background: Haemodynamic measurements may be superior to the 6-min walk distance (6MWD) as outcome measures in pulmonary hypertension (PH) as they are directly linked to the mechanisms of disease and are not subject to a ceiling effect. The aim of this study was to determine if treatment response in precapillary PH could be detected by pulmonary blood flow (PBF) and stroke volume (SV) measured non-invasively by the inert gas rebreathing (IGR) method at rest and during submaximal constant-load cycle exercise. Methods: Twenty-four patients with precapillary PH receiving de novo or modified disease-targeted therapy were studied. Isotime metabolic variables, PBF and SV were measured at rest and during constant-load cycle exercise at 40% maximal work rate alongside conventional outcome variables, at baseline and after 3 months of new therapy. Results: At follow-up there was a significant increase in PBF (supine rest: mean 0.7±SD 0.9 l/min, erect rest: 0.7±0.8 l/min, exercise: 0.8±1.0 l/min, p<0.005) and SV (supine rest: 7±10 ml, erect rest: 10±11 ml, exercise: median 6 (IQR 3–11) ml, p<0.005). There was a trend for 6MWD to increase by 17±42 or 29 (13–47) m (p=0.061), whereas WHO functional class, N-terminal pro-brain natriuretic peptide or Cambridge Pulmonary Hypertension Outcome Review score were unchanged. In patients with higher baseline 6MWD, IGR measurements were more sensitive than 6MWD in detecting treatment response. Conclusions: Non-invasive IGR haemodynamic measurements could be used to detect treatment response in patients with precapillary PH and may be more responsive to change than 6MWD in fitter patients.